The epigenomic basis of common diseases. Issue 1 (December 2017) - Rodger, Euan; Chatterjee, Aniruddha
Abstract A report of the 6th Epigenomics of Common Diseases Conference held at the Wellcome Genome Campus in Hinxton, Cambridge, UK, on 1–4 November 2016.